Analisis Efek Senam Kaki Terhadap Sensitifitas Kaki pada Pasien Diabetes Di Wilayah Kerja Puskesmas Alai Padang - Putri Dafriani; Siti Aisyah Nur; Welly Martawati (Jurnal Kesehatan Medika Saintika, 2019)
Neuropathy or neurological disorders are caused by hyperglycemia. It can cause damage to the peripheral nervous system. It makes diabetic patients cannot feel heat, pain and tingling. The aim of this research to determine the effect of foot exercise on foot sensitivity at diabetic patients in Puskesmas Alai Kota Padang. This type of research is quasi-experimental, one group pretest postest. Sample was 16 diabetic patients in Puskesmas Alai. The data were processed by computerization with univariate analysis using descriptive statistics and bivariate analysis using the Wilcoxon Signed Ranks Test.  The results of univariate analysis showed an average foot sensitivity before foot exercise was 1,56 and after that was 2,44. The results of bivariate analysis showed that there was an effect with p = 0,000 (p≤0,05). Based on the results, this study proved the effect of foot exercise in diabetic patients. It suggested to facilitate foot exercise at diabetic patients by nurses in Puskesmas Alai.